ANALISIS PERSEDIAAN BAHAN BAKU POZZOLAN PADA PT SEMEN BATURAJA - Fredy Novianto, Philipus; Safaruddin, Safaruddin; Furwanto, Edi (JIM : Journal Of International Management, 2022)
The supply of raw materials is closely related to the number of requests for products produced and the amount of use of the amount of raw materials available to carry out the production process. During the process of shipping Pozzolan raw materials originating from Muaradua which is located in South Ogan Komering Ulu Regency, South Sumatra, Indonesia where the delivery of raw materials must use goods transportation services via land transportation. The problems that occur during the delivery and mining of Pozzolan raw materials. Which if the rainy season can make it difficult for vendors to get Pozzolan raw materials in the mining area and also the slippery road to the mine site, making it difficult for trucks to carry out the process of transporting Pozzolan raw materials to PT. Semen Baturaja (Persero) Tbk. This situation makes the supply of raw materials uncertain. While the inventory has been calculated safety stock, minimum inventory, maximum inventory. If this activity continues, it will hamper the Company in carrying out its production process activities and affect safety stock, minimum inventory and maximum inventory.